Valuing Electricity Service Attributes: A Choice Experiment Study in Madhya Pradesh, India - Herath Gunatilake; Sumeet Patail; Jui Chen Yang (Asian Development Bank (ADB), 2012)
This paper presents the results of a choice experiment study undertaken to value electricity service attributes in Madhya Pradesh, India. Primary data was collected from 2,083 households using stratified random sampling method. Results show that existing service is very poor and consumers have substantial willingness to pay (WTP) for changing the status quo. Amongs the studied service attributes, hours of supply captures the highest WTP and WTP declines significantly with reduced hours of supply. However, quality, customer service, and accuracy of billing together accounts for 56% of the total WTP. Assessment of WTP with different service attribute combinations show that value of other service attributes become relatively more important when supply is less than 24 hours. Simulations show that uptake rates increase substantially when improved hours of supply is supplemented with other service attributes. Development impact of 1.2 billion worth physical infrastructure investments on Madhya Pradesh power distribution network for 24-hour supply can be significantly enhanced if quality, customer service, transparency, and accuracy of billing are also improved simultaneously.
hdl:11540/1265
Keywords: 330; Energieversorgung; Netzinfrastruktur; Zahlungsbereitschaftsanalyse; Ländlicher Raum; Madhya Pradesh; Indien